Fatigue Performance of Laser Welds in Heavy-Gage Press Hardening Steels - Diego Tolotti de Almeida; Kleber Eduardo Bianchi; João Henrique Corrêa de Souza; Milton Sergio Fernandes de Lima; Thomas Gabriel Rosauro Clarke; Fabio Pinto da Silva; Hardy Mohrbacher (Metals, 2022)
This work investigates and compares the fatigue performance of laser-welded joints of two press hardening steels: a standard 22MnB5 and a variant modified by a combination of niobium and molybdenum (NbMo) alloying. The results indicate that joint geometry aspects, superposed to an intrusion-generated damage mechanism, were prevalent in causing a poor fatigue life in the case of peak stress values greater than 11% of the base metal's ultimate strength being around 1450 MPa. As identical process procedures were employed, the tests allowed investigating the influence of the alloy design on fatigue performance. The results of geometrical analysis and fatigue tests indicated that the NbMo modified alloy performed better than the standard 22MnB5 steel. The results also suggest that, if extremely tight quality limits are used in the manufacturing procedures, laser-welded joints of press hardened steels could offer a very favorable fatigue performance being considerably better than that of conventional and high strength structural steels.